What is the emotional core of the multidimensional Machiavellian personality trait? - Al Aïn, Syrina; Carré, Arnaud; Fantini-Hauwel, Carole; Baudouin, Jean-Yves; Besche-Richard, Chrystel (Frontiers in Psychology, 2013)
Machiavellianism is a personality trait characterized by interpersonal manipulation and associated with specific patterns of emotional and social cognition skills. The aim of this study was to investigate its socio-cognitive characteristics by determining its association and predictors on the basis of a multidimensional approach to Machiavellianism. We used Mach IV scale to assess ‘‘Machiavellian Intelligence’’ skill of participants (Christie & Geis, 1970). It includes three subscales that are 1) the use of deceit in interpersonal relationships, 2) a cynical view of human nature and 3) the lack of morality. Associations were found between Machiavellianism and low levels of empathy and affective ToM, and high levels of alexithymia, anhedonia, depression, and anxiety. These associations were observed in varying proportions depending on the three subscales of Machiavellianism. The addition of anhedonia and trait-anxiety to the concepts of empathy and alexithymia made it possible to gain a better understanding of the emotional core of Machiavellianism. These findings are discussed in the light of developmental and adaptive perspectives.